Turning traditions upside down : rethinking Giordano Bruno's enlightenment - Hufnagel, Henning S.; Eusterschulte, Anne (Central European University Press, 2012)
In this book, eminent researchers on Bruno offer an overview of the state-of-the-art research on his work, discussing Bruno's methodological procedures, his epistemic and literary practices, his natural philosophy, or his role as theologian and metaphysic at the cutting-edge of their disciplines. Short texts by Bruno illustrate the reasoning of the contributions. The book also reflects aspects of Bruno's reception in the past and in the twenty-first century, inside and outside academia.